Rapid agglutination test for the detection of infections bursal disease virus antigen - GOWRI, A MANGALA; KUMAR, R JAYA; KUMANAN, K; NACHIMUTHU, K (The Indian Journal of Animal Sciences, 2013)
An attempt has been made using the particle agglutination principles by coating immunoglobulins on latex beads for the rapid diagnosis of infectious bursal disease (IBD) viral antigen. Efficacy of the developed latex agglutination(LAT)was compared with the OlE approved agar gel immuno diffusion (AGID) test Latex agglutination test was 94 % sensitive and 70 % specific and has got 90 % concordance with that of the standard test. The sensitivity was also nonsignificant in antigen detection and highly correlated with that of the standard test. Thus LAT could be used as a sensitive, penside field diagnostic test for IBDV antigen detection.